2021
DOI: 10.1200/jco.2021.39.15_suppl.e16104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience: FOLFIRI/XELIRI after failure of a fluoropyrimidine/platinum combination regimen in advanced gastroesophageal adenocarcinoma.

Abstract: e16104 Background: Portugal has the highest gastric cancer incidence in western Europe. In our institution, FOLFIRI/XELIRI is the standard second line (2L) chemotherapy (CT) in advanced gastroesophageal adenocarcinoma (aGEA). Other treatment option is paclitaxel/ramucirumab combination. There is no prospective trial comparing these regimens. Our global aim was to investigate efficacy and safety of FOLFIRI/XELIRI after failure of a fluoropyrimidine/platinum (FP) regimen in patients with aGEA. Methods: Single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Efficacy outcomes were similar to the ones reported for the paclitaxel/ramucirumab combination RAINBOW trial. [ 21 ] Previous studies reported that the use of ramucirumab in combination with FOLFIRI showed favourable progression-free survival and overall survival in patients with prior treatments with platinum and/or taxane-based agents and allowed further treatment lines after progression. In patients with taxane pretreatment or persistent high-grade PNP, the combination of FOLFIRI-R might be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy outcomes were similar to the ones reported for the paclitaxel/ramucirumab combination RAINBOW trial. [ 21 ] Previous studies reported that the use of ramucirumab in combination with FOLFIRI showed favourable progression-free survival and overall survival in patients with prior treatments with platinum and/or taxane-based agents and allowed further treatment lines after progression. In patients with taxane pretreatment or persistent high-grade PNP, the combination of FOLFIRI-R might be promising.…”
Section: Discussionmentioning
confidence: 99%